Early versus late laparoscopic cholecystectomy in the management of acute cholecystitis: a retrospective study - Thiyagarajan, Deepu; Ruban, Prince Deva (International Surgery Journal, 2019)
Background: Early laparoscopic cholecystectomy (LC) is a life-saving procedure in the management of acute cholecystitis as it helps in prevention of late complications like development of adhesions, haemorrhage and sepsis. The study aims at comparing the outcomes of early versus late laparoscopic cholecystectomy in the management of acute cholecystitis. Methods: A retrospective study was done by analyzing the past 5 years medical records of 250 patients admitted to the emergency department with diagnosis of acute cholecystitis established according to the Tokyo criteria. The relevant clinio-social demographic data of the patients, clinical and radiological parameters, intra-operative and post-operative findings and follow-up data were compared between early and late LC group of patients. Results: The study included 125 middle aged patients who underwent early LC (within 24 hours) and 125 patients who underwent late LC (after 24 4hours). The complication rate, conversion to open cholecystectomy and duration of surgery showed no significant differences between early and late laparoscopic cholecystectomy except for an increased duration of stay among the late LC group. Conclusions: Early LC is an efficient procedure for acute cholecystitis but it has risks of complications which can be minimized by careful selection of patients after clear clinical and radiological evaluation.